1985
DOI: 10.1128/aem.50.4.984-988.1985
|View full text |Cite
|
Sign up to set email alerts
|

Micro-lipid-droplet encapsulation of Bacillus thuringiensis subsp. israelensis delta-endotoxin for control of mosquito larvae

Abstract: The crystal 8-endotoxin of Bacillus thuringiensis subsp. israelensis is less toxic to larvae of Anopheles freeborni than to larvae of Aedes aegypti. However, when solubilized crystal was used, larvae from both species showed similar sensitivities. This effect presumably was due to the differences in feeding behavior between the two mosquito larvae when crystal preparations are used. A procedure is described whereby both crystal and solubilized B. thuringiensis subsp. israelensis toxin were emulsified with Freu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 14 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…68 In the literature, we found some works that have been reported the microencapsulation of Bt in different matrices. For example, Cheung and Hammock 69 studied the encapsu- Bt biopesticide was prepared using graphene oxide nanosheets and olive oil as protectors against UV radiation; evaluation was made of the viability of the spores and the protective effect against UV radiation, together with bioassays employing Ephestia kuehniella; the results showed that use of the combination resulted in viability greater than 50% after exposure to UV radiation for 96 h, while spores without the protectors presented viability of 32.54%; the mortality obtained using the formulation was also higher, with a value of 68.89% compared to 40% for the free spores Bt nanotubes sodium titanate investigation was made of the ability of sodium titanate nanotubes to potentiate the activity of Bt; the biological activity was investigated against Spodoptera littoralis; scanning electron microscopy (SEM) images showed adsorption of the nanotubes on the bacterial surface, revealing the success of the interaction; the biological tests showed that the hybrid system significantly affected some biological parameters, such as larval and pupal duration, adult fertility, larval and pupal malformation, adult longevity, and adult sex ratio 100 Cry1Ac toxin from Bt nanoparticles magnesium hydroxide magnesium hydroxide nanoparticles were synthesized for control of the loss of the Cry1Ac protein and increased effectiveness against Helicoverpa armigera; the results showed that the toxin was successfully loaded in the nanoparticles by electrostatic adsorption; the nanoparticle system showed greater capacity to remain on the surfaces of cotton sheets (adhesion greater than 59%), resulting in a 75% increase of pest mortality; other important findings were that the nanoparticles could be decomposed by acid and that they did not present phytotoxicity to cotton Bt KCTC 1508 strain microparticles mucopolysaccharide concentrate invention is a formulation based on the microbial insecticide of Bt; the inventors used a mucopolysaccharide concentrate to encapsulate and protect the bacteria; in addition to this material, they also describe a variety of other components that can be added to the formulation, such as sunscreen agents and spreading agents; this formulation presents insecticidal activity against different insect pests and exhibits excellent stability 102…”
Section: Encapsulation Strategies For Bmentioning
confidence: 99%
“…68 In the literature, we found some works that have been reported the microencapsulation of Bt in different matrices. For example, Cheung and Hammock 69 studied the encapsu- Bt biopesticide was prepared using graphene oxide nanosheets and olive oil as protectors against UV radiation; evaluation was made of the viability of the spores and the protective effect against UV radiation, together with bioassays employing Ephestia kuehniella; the results showed that use of the combination resulted in viability greater than 50% after exposure to UV radiation for 96 h, while spores without the protectors presented viability of 32.54%; the mortality obtained using the formulation was also higher, with a value of 68.89% compared to 40% for the free spores Bt nanotubes sodium titanate investigation was made of the ability of sodium titanate nanotubes to potentiate the activity of Bt; the biological activity was investigated against Spodoptera littoralis; scanning electron microscopy (SEM) images showed adsorption of the nanotubes on the bacterial surface, revealing the success of the interaction; the biological tests showed that the hybrid system significantly affected some biological parameters, such as larval and pupal duration, adult fertility, larval and pupal malformation, adult longevity, and adult sex ratio 100 Cry1Ac toxin from Bt nanoparticles magnesium hydroxide magnesium hydroxide nanoparticles were synthesized for control of the loss of the Cry1Ac protein and increased effectiveness against Helicoverpa armigera; the results showed that the toxin was successfully loaded in the nanoparticles by electrostatic adsorption; the nanoparticle system showed greater capacity to remain on the surfaces of cotton sheets (adhesion greater than 59%), resulting in a 75% increase of pest mortality; other important findings were that the nanoparticles could be decomposed by acid and that they did not present phytotoxicity to cotton Bt KCTC 1508 strain microparticles mucopolysaccharide concentrate invention is a formulation based on the microbial insecticide of Bt; the inventors used a mucopolysaccharide concentrate to encapsulate and protect the bacteria; in addition to this material, they also describe a variety of other components that can be added to the formulation, such as sunscreen agents and spreading agents; this formulation presents insecticidal activity against different insect pests and exhibits excellent stability 102…”
Section: Encapsulation Strategies For Bmentioning
confidence: 99%
“…Bacterial particles which leave the surface region are not available for ingestion by mosquito larvae, particularly Anopheles larvae, which feed at the water surface (126). The development of floating formulations is desirable, and several types have been tested in the laboratory and in the field (6,37,109,119). With the microlipid droplet encapsulation method, B. thunngiensis subsp.…”
Section: Formulationmentioning
confidence: 99%
“…With the microlipid droplet encapsulation method, B. thunngiensis subsp. israelensis was made equally effective againstAnopheles and Culex larvae, unlike the nonencapsulated method, which gave much lower activity against Anopheles larvae (37). Similarly, other floating-type formulations had significantly increased activity against Anopheles larvae (6).…”
Section: Formulationmentioning
confidence: 99%
“…The toxicity of native crystals against mosquito larvae ranges from 0-2-5 ng ml-l (Thomas & Ellar, 1983;Yamamoto et al, 1983). Because mosquito larvae are filter feeders, the soluble proteins have been attached to latex beads (Schnell et al, 1984), encapsulated (Cheung & Hammock, '1985) or precipitated (Insell & Fitz-James, 1985) to increase the amount of the protein ingested by the larvae. Reported LCs0 values for the purified components are 40 ng ml-1 for the 130 kDa doublet (Visser et al, 1986), 43-600 ng ml-l for the 65 kDa protein (Insell & Fitz-James, 1985;Ibarra & Federici, 1986) and 125-1000 ng ml-1 (Visser et al, 1986;Ward et al, 1986) for the 27 kDa protein.…”
Section: Introductionmentioning
confidence: 99%